2014
DOI: 10.1186/s40557-014-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between working condition factors and well-being

Abstract: ObjectivesWorking conditions can exert influence on the physical, mental, and even social health of workers. Well-being is an appropriate index for the evaluation of a person’s overall health. This paper investigated the association between various working conditions and worker’s well-being.MethodsData from 10,019 interviews were collected from the second wave of the Korean Working Conditions Survey (2010) conducted by the Korea Occupational Safety and Health Agency between June and October 2010. The data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
(28 reference statements)
3
16
0
Order By: Relevance
“…Our finding also suggests that subjects who were over 40 years old significantly tended to have a lower psychological well-being. This finding is consistent with a previous study that older subjects tended to have a lower well-being [ 36 ] but contradicts the findings that older individuals are happier with their lives than younger individuals [ 39 ]. In stratified by age, the unadjusted ORs of poor psychological well-being for all age group were significantly higher for SHS exposure group compared to reference group.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our finding also suggests that subjects who were over 40 years old significantly tended to have a lower psychological well-being. This finding is consistent with a previous study that older subjects tended to have a lower well-being [ 36 ] but contradicts the findings that older individuals are happier with their lives than younger individuals [ 39 ]. In stratified by age, the unadjusted ORs of poor psychological well-being for all age group were significantly higher for SHS exposure group compared to reference group.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies drawn from the KCWS showed other results, suggesting that the well-being of all subjects yielded no differences between the genders [ 36 , 38 ]. But, we found that females tended to have a lower well-being than males.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This principle factor of working condition is extremely significant to improve the productivity and respect of the workers on construction sites. According to Lee et al [17], working conditions have a substantial influence on the workers' quality of life, and workers spend more than a half of their working hours at a project site. Therefore, the working conditions influence the life of the workers, this might be the reason why the respondents did not rate the scale of 1 (SD) in all the five factors.…”
Section: Results Analysis and Interpretationmentioning
confidence: 99%
“…Working condition of equipment [28] is the condition in which the equipment works, including but not limited to such things as amenities, physical environment, stress and noise levels, degree of safety or danger, and the like. The working condition diagnosis usually uses specific models or variables for different applications.…”
Section: Working Condition Diagnosismentioning
confidence: 99%